Fostering the Teachers Rediness for Using the Informational Educational Environment in Higher Scool - N. V. Lomovtseva; E. V. Tchubarkova; A. A. Karasik (Russian State Vocational Pedagogical University, 2015)
The paper proves the necessity of teachers' readiness for introduction of the informational education environment to the higher school teaching process. The dynamic implementation of information communication and distance education technologies gives way to the more advanced level of pedagogic activity by broadening the teachers' didactic, informational, methodological and technological horizons, and improving, therefore, the impact of education. The authors indicate the functional specifics of informational education environment that is designed to provide the full range of services and facilities for planning the student's self-study work, consultations and controls. The components of teachers' readiness for using information technologies in their daily professional work are defined including the motivational, technological, emotional, volitional, communicative and reflexive ones. The pedagogical tasks concerning the application of informational education environment along with organizational terms are outlined.